Exigência de lisina digestível para codornas japonesas na fase de crescimento: efeitos da técnica de formulação das dietas e da modelagem matemática nos valores estimados - Felix, Tamires Marcelino da Silva (2020)
This work aimed to estimate the requirement for digestible lysine for growing Japanese quails by evaluating the influence of the diet formulation technique: supplementation and dilution, and of the regression models: Linear Response Plateau (LRP), Polynomial Quadratic (PQ) , intersection of LRP∩QP, Quadratic with Plateau Response (QPR) and Exponential (EXP). For this, 684 Japanese quails (10 to 36 days old) with initial weight of 33.7±0.42g were used, housed in overlapping cages and distributed in a completely randomized design in a 2x7 factorial arrangement, two formulation techniques (supplementation technique and dilution technique) and seven levels of lysine (0.70; 0.80; 0.90; 1.00; 1.10; 1.20 and 1.30%), thus composing 14 treatments. Performance parameters, carcass components and nutrient gain were evaluated. There was interaction (p <0.05) between the formulation techniques and the levels of digestible lysine tested for feed intake (FI), lysine intake (ILys), weight gain (WG), feed conversion (FC), carcass weight (CW), crude protein gain (CPG) and crude fat gain (CFG), in addition to the isolated effect of the formulation technique on percentage of legs (LEG). The application of the dilution technique resulted in a greater discrepancy between the values of FI, lower WG and CW, worse FC, and lower efficiency in the deposition of nutrients (CPG and CFG), however they presented higher LEG. The digestible lysine requirement values estimated for better performance and efficiency in nutrient deposition were 0.98% by the supplementation technique and 1.15% by the dilution technique. The best estimates were obtained through the intersection of the LRP∩QP and the QP model, the LRP model underestimated the values while the EXP model overestimated. It can be concluded that the requirement for digestible lysine in Japanese quails is influenced by the formulation technique and by the mathematical model used in the interpretation of the data.